2017
DOI: 10.1038/srep41441
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation with alginate/CaCO3: A strategy for improved phage therapy

Abstract: Bacteriophages are promising therapeutic agents that can be applied to different stages of the commercial food chain. In this sense, bacteriophages can be orally administered to farm animals to protect them against intestinal pathogens. However, the low pH of the stomach, the activities of bile and intestinal tract enzymes limit the efficacy of the phages. This study demonstrates the utility of an alginate/CaCO3 encapsulation method suitable for bacteriophages with different morphologies and to yield encapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 37 publications
5
87
0
3
Order By: Relevance
“…A number of previous studies have used alginate as the main encapsulating agent either on its own [37], [63], [64] or in combination with whey protein [32], [60], [61] or chitosan [31], [33]. Phages encapsulated in crosslinked pure alginate microparticles were found to be susceptible to acid damage following exposure to simulated gastric fluid [31], [37], [62].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of previous studies have used alginate as the main encapsulating agent either on its own [37], [63], [64] or in combination with whey protein [32], [60], [61] or chitosan [31], [33]. Phages encapsulated in crosslinked pure alginate microparticles were found to be susceptible to acid damage following exposure to simulated gastric fluid [31], [37], [62].…”
Section: Discussionmentioning
confidence: 99%
“…The porosity of the alginate gel microparticles affects phage susceptibility to acid damage due to diffusion of acid. A number of studies have added CaCO 3 within the microparticles to protect phage from acid damage [37], [63]. Other studies have shown that by combining alginate with chitosan [31], [80] or whey protein [32], [60], [61], better acid protection may be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kontrol grubu enfekte tavuklar ile serbest ve mikrokapsüle bakteriyofaj karışımı verilen enfekte tavukların kör bağırsaklarında 15 günün sonunda S. typhimurium ATCC14028 Rif R sayısı sırasıyla 5.2±1.3, 6.3±1.0 ve 3.5±2.1 log kob/g olarak tespit edilmiştir. Çalışmanın sonucunda Salmonella ile enfekte olan ticari broiler tavuklarda ağız yoluyla faj terapisinin başarıyla uygulandığı değerlendirilmiştir [32].…”
Section: Bakteri̇yofajlarin Mi̇krokapsülasyonu Ve In Vitro Gastroi̇ntestunclassified